Perlindungan Hukum Terhadap Anak Korban Tindak Pidana Kekerasan Seksual - Syuha Maisytho Probilla; Andi Najemi; Aga Anum Prayudi (PAMPAS: Journal of Criminal Law, 2021)
This article explains 1) Child as victim of sexual violence in the case of WA did not obtain legal protection as from the beginning the victim was declared as the perpetrator rather than as a victim. The victim was granted status as the perpetrator until the court verdict imposed a crime and the victim had served the sentence at LPKA. The victim received post-adjudication legal assistance after being accompanied by a Legal Counsel. 2) The obstacles faced so that child victims did not obtain legal protection is due to the lack of sensitivity by the UPTD PPA in understanding the "specificity" contained in the case of WA, where WA is not only the perpetrator but the victim as well whose rights must be fulfilled. It is necessary to include basic regulations regarding the UPTD PPA in the provisions of Act Number 35 Year 2014 on the Amendments to Act Number 23 Year 2002 on Child Protection as a form of strengthening the institutional existence of UPTD PPA. The UPTD PPA must be more proactive and sensitive to developments in cases of sexual violence in Indonesia and improve facilities and infrastructure that will support the fulfillment of protection for victims of sexual violences in order to be more optimal. Abstrak Artikel ini menjelaskan 1) Anak korban WA tidak mendapatkan perlindungan hukum karena sejak awal Anak korban dinyatakan sebagai pelaku, bukan sebagai korban. Status korban sebagai pelaku, sampai putusan pengadilan menjatuhkan pidana dan korban sempat menjalani masa pidananya di LPKA. Korban baru mendapat pendampingan secara hukum setelah didampingi Penasihat Hukum post ajudikasi. 2) Kendala yang dihadapi sehingga Anak korban tidak mendapatkan perlindungan hukum dikarenakan kurangnya sensitifitas UPTD PPA dalam melihat â€œkekhususanâ€ yang terdapat dalam kasus WA, dimana WA tidak hanya sebagai pelaku tetapi juga korban yang harus dipenuhi hak-haknya. Saran: Perlu dimuatnya pengaturan secara pokok mengenai UPTD PPA dalam ketentuan Undang-Undang Nomor 35 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak sebagai bentuk penguatan eksistensi kelembagaan UPTD PPA. UPTD PPA harus lebih proaktif dan sensitif terhadap perkembangan kasus kekerasan seksual di Indonesia serta meningkatkan sarana dan prasarana yang akan mendukung pemenuhan perlindungan terhadap korban tindak pidana kekerasan seksual agar menjadi lebih optimal.